DNA Vaccines Targeting Novel Cancer-Associated Antigens Frequently Expressed in Head and Neck Cancer Enhance the Efficacy of Checkpoint Inhibitor - Wang, Chuan; Zainal, Nur Syafinaz; Chai, San Jiun; Dickie, James; Gan, Chai Phei; Zulaziz, Natasha; Lye, Bryan Kit Weng; Sutavani, Ruhcha V.; Ottensmeier, Christian H.; King, Emma V.; Abraham, Mannil Thomas; Ismail, Siti Mazlipah binti; et al. (Frontiers in Immunology, 2021)
HPV-independent head and neck squamous cell carcinoma (HNSCC) is a common cancer globally. The overall response rate to anti-PD1 checkpoint inhibitors (CPIs) in HNSCC is ~16%. One major factor influencing the effectiveness of CPI is the level of tumour infiltrating T cells (TILs). Converting TILlow tumours to TILhigh tumours is thus critical to improve clinical outcome. Here we describe a novel DNA vaccine to facilitate the T-cell infiltration and control tumour growth. We evaluated the expression of target antigens and their respective immunogenicity in HNSCC patients. The efficacy of DNA vaccines targeting these two antigens were evaluated with or without CPI using a syngeneic model. Most HNSCC patients (43/44) co-expressed MAGED4B and FJX1 and their respective tetramer-specific T cells were in the range of 0.06-0.12%. In a preclinical model, antigen-specific T cells were induced by DNA vaccines and increased T cell infiltration into the tumour, but not MDSC and regulatory T cells. The vaccine inhibited tumour growth and improved the outcome alone and upon combination with anti-PD1 resulted in tumour clearance in approximately 75% of mice. Pre-existence of MAGED4B and FJX1-reactive T cells in HNSCC patients suggests that these widely expressed antigens are highly immunogenic and could be further expanded by vaccination. The DNA vaccines targeting these antigens induced robust T cell responses and synergised with the anti-PD1 antibody conferring excellent tumour control. This opens up an opportunity for combination immunotherapy that might benefit a wider population of HNSCC patients in an antigen-specific manner.